The Indian River that Flows from Paradise - Di Serio, Chiara (Studia Ceranea, 2022)
In the Jewish Antiquities (I, 1, 3), when paraphrasing the passage of Genesis 2, 10–15, Flavius Josephus notes that the four rivers springing in paradise are the Phison (Φεισὼν), which passes through India and is called Ganges by the Greeks, the Euphrates and Tigris, which flow into the Red Sea, and finally the Geon, which crosses Egypt and is called the Nile by the Greeks. Starting from Josephus’ comments, this research focuses on the various interpretations of the Genesis passage, and in particular on the references to the Phison in the writings of the hellenised Jewish and Christian authors. The contents of these texts show common traits with Greco-Roman sources that describe India as a utopian space outside of history. Therefore, the analysis of the documents reveals how a sequence of texts developed over the centuries, starting from a utopian image of India and reaching a definition of a land close to paradise.